PENGARUH ALGORITMA DAN LIVE STREAMING TIKTOK TERHADAP IMPULSE BUYING KONSUMEN FASHION DI TIKTOK SHOP - Wuri Purnamasari; Beny Hayato (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2026)
This study aims to analyze the influence of algorithms and live streaming on the impulse buying behavior of fashion consumers on TikTok Shop. The study employed a quantitative approach using primary data collected through an online questionnaire distributed via Google Forms to 100 respondents selected using a purposive sampling technique. Data were analyzed using SPSS version 30 through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test (partial), F-test (simultaneous), and the coefficient of determination (R Square). The results indicate that the algorithm variable does not have a significant effect on the impulse buying behavior of fashion consumers on TikTok Shop, with a significance value of 0.102 (>0.05). In contrast, the live streaming variable has a positive and significant effect on impulse buying, with a regression coefficient of 0.559 and a significance value of <0.001 (<0.05). Simultaneously, algorithms and live streaming have a significant effect on impulse buying, as evidenced by an F-statistic of 46.753 and a significance value of <0.001. The coefficient of determination (R Square) of 0.491 indicates that the two independent variables explain 49.1% of the variation in impulse buying, while the remaining 50.9% is influenced by other factors outside the research model. These findings suggest that live streaming is a more dominant factor than algorithms in encouraging consumers to make impulsive purchases on TikTok Shop.